Determination of Fermentation Characteristics of a Total Mixed Ration Prepared with Maize Forage with Different Dry Matter Contents - Hande Işıl Akbağ; Emre Gezgin; Soner Yiğit; Hakan Erdem (Turkish Journal of Agriculture: Food Science and Technology, 2025)
This study aims to assess the effects of silage on the quality characteristics and aerobic stability of total mixed rations (TMR) made with maize forage that have different dry matter (DM) contents. For this purpose, TMRs prepared using maize forage with two different dry matter (low dry matter (29.6 %); LDM, high dry matter (39.66 %); HDM) levels were divided into two groups. All groups were subjected to an aerobic stability test for 5 days at the end of the 45-day fermentation period. Aerobic stability tests of five repetitively generated TMR silages were determined by measuring internal temperatures through data loggers. During this process, chemical analysis, pH, and microbiological analysis were performed daily. It was determined that pH, crude protein (CP), acide detergent lignin (ADL), and dry matter (DM) concentrations of ensilled and unensilled TMR samples were affected by group x day interaction (P≤0.05). The pH values in TMR samples increased during aerobic stability, but they were more noticeable in unensilled groups (P≤0.05). The internal and ambient temperature values in ensilled TMR remain within the confidence intervals. On the contrary, the temperature values of unensilled TMR samples have been determined to be higher than ambient temperature values (P≤0.05). Under aerobic conditions, unensilled TMR silages deteriorated rapidly. Therefore, the addition of high dry matter corn forage to TMR and esilled of TMR is more suitable for both good fermentation quality and resistance to aerobic deteriation. There is a need for studies to determine the aerobic deterioration and digestibility properties of TMR silages with different dry matter contents.